Affordance perception of elderly people on the straddling over hurdles: On the effects of visual condition - Ito, Tomoaki; Ono, Akira; Morita, Yohei; Watanabe, Shinichi; Fukushima, Kazuyuki; Akutu, Takanobu; Miyashita, Mitsumasa (Structure and Function, 2019)
The purpose of this research was to clarify the vertical straddling affordance of elderly people. Subjects were 13 healthy elderly men (mean age, 63.1 ± 3.0 years) and 16 young men (mean age, 25.1 ± 5.0 years). The data of measurements were the height of a bar over which the subject considered to be able to straddle. The bar was set up at seven meters away from the subject, and gradually raised it until the subject declare the limit highest of the bar. Conditions were to straddle over the bar (1) With one (side) eye open with both eyes open, (2) with eye open, and (3) with goggle designed for the elderly. The data correspond to the maximum value that was able to straddle. The affordance value was calculated by the formula of the open-eye condition predicted values derided by the leg length. Overestimation and underestimation of prediction were calculated by predicted values derided by measured values. The main results obtained were as follows. (1) The predicted average values were lower in both groups in the order with the open eye, one eye, and experiential elderly goggles. However, the older group showed lower values than the younger group. (2) The affordance value was 0.84 in the younger group and 0.75 in the elderly group (per lower arm length). (3) Predicted values over observed values were underestimated as 0.89 for younger groups and 0.80 for elderly groups, showing no significant differences. (4) Most importantly, for elderly people, affordance values showed in order with open eye , one eye and experiential elderly goggles.These results suggested that visual conditions were important to predict the height of a straddle motion. This tendency seems significant in the elderly group than in the younger group.